Assessing the Conditions for the Occurrence of Unintentional Injections among Nurses and the Prospects for the Use of Safe Devices - E. V. Glushkova; A. Yu. Brazhnikov; A. Yu. Kamenskaya; A. D. Repetyuk; R. V. Polibin (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. Sharp instrument injuries among medical workers are a serious health problem in all countries of the world. There is no official registration of needle sticks injuries among medical workers in Russia and this is a problem.Aim. To assess the knowledge and commitment of nurses about safety procedures (infusion therapy, venipuncture and injections), to identify the frequency of unintentional injections associated with these procedures, their causes, staff awareness of the existence of safe devices.Materials and methods. A total of 1,189 nurses from 169 Russian cities participated in the study. Among the surveyed nurses, 1109 (93.27%) work only in state institutions and 80 (6.73%) combine work in state and private institutions. The majority (56.52%) had more than 15 years of experience in their specialty, 24.81% had 6-15 years of experience, and 18.67% had 0-5 years of experience. Of those surveyed, 67.03% performed infusions, 75.19% performed venipunctures, and 96.89% performed injections.Results. In our study the most dangerous procedure was infusion therapy (21.58% of nurses reported needle sticks during the procedure). More than 40% of injuries were caused by the patient movement during the procedure. Health care workers often reported unintentional injections during the disposal phase of infusions and injections (40.70% and 43.31%, respectively), and the most dangerous step being manual disassembly of the stabbing instrument (25.98% and 21.51%, respectively). In 50.63% of nurses, unintentional injections were reported during venipuncture, after removal of the needle from the vein and before disposal. According to the survey results, only two thirds of nurses are informed about the existence of peripheral venous catheters with a needle protection mechanism, safe devices / needles for blood sampling from a vein, and 53.94% are informed about the existence of injection needles with a protection mechanism. Every nurse should know the correct procedure for the procedure and a set of measures in cases of unintentional needle sticks. However, more than 30% of respondents reported that they didn’t receive procedure safety training.Conclusion. The use of safe devices during infusion therapy, venipuncture and injection would eliminate cases of unintentional injections at the most dangerous stages of these procedures, because of the presence of device protection mechanism, which closes the needle immediately after the procedure and protects the medical worker from further injury.